PERBANDINGAN HUKUM PENYELESAIAN SENGKETA ARBITRASE DALAM MASA PANDEMI COVID-19 - Dea Tunggaesti (Jurnal Hukum dan Bisnis (Selisik), 2021)
Pandemic Covid-19 that occur globally is causing a lot of difficulties and obstacles in all aspects. With this resulted in restrictions on the movement of people, social distancing and closing a total of offices and even have an impact on litigation in the national courts. That the application of the trial of the online arbitration institutions has not been done entirely by the Indonesian National board of Arbitration and how the legal certainty of the parties. That the lack of legal protection for the trial of the online in the Supreme Court Regulation No. 1 of 2019 about Methods of Electronic Trials the Arbitration institution should be able to conduct trials online and with the agreement of the parties, then the legal certainty of the parties will also be guaranteed if such things are done in an open and an agreement between both parties